Chirality assignment of single-walled carbon nanotubes with strain - Li, L; Nicholas, R; Deacon, R; Shields, P; Chen, C; Darton, R; Baker, S (2005)
Strain-induced band gap shifts that depend strongly on the chiral angle have been observed by optical spectroscopy in polyvinylpyrrolidone(PVP)- or Surfactin micelle-wrapped single-walled carbon nanotubes (SWCNTs). Uniaxial and torsional strains are generated by changing the environment surrounding the SWCNTs, using the surrounding D2O ice temperature or the hydration state of a wrapping polymer. These methods can be used as diagnostic tools to determine the quantum number, q, and examine chiral vector indices for specific nanotube species.